Allergen challenge in allergic rhinitis rapidly induces increased peripheral blood ILC2 which express CD84 - Doherty, Taylor A. (2014)
Type 2 innate lymphoid cells (ILC2) produce high levels of Th2 cytokines. Our study demonstrates that cat allergen challenge in allergic rhinitis subjects rapidly induces increased peripheral blood ILC2.